Forecasting the Demand and Supply of Technicians in Construction - Sing, Michael; Love, Peter; Tam, C. (American Society of Civil Engineers, 2014)
Workforce forecasting is a strategic managerial practice that construction organizations should implement to ensure a balanced workplace. The workforce forecasting systems that have been developed are either qualitative or quantitative in nature. This paper develops a sustainable workforce model that utilizes both quantitative and qualitative data to improve the accuracy of workforce demand and supply forecasts. Using empirically derived data for off-site construction technicians in Hong Kong, the developed workforce forecasting system is used as a strategic managerial tool to predict and monitor workforce conditions.